P.143 How well can neuroradiologists localize clinical signs?. (November 2021) - Curtis, C; Pauranik, A
Abstract : Background: A basic understanding of localization for a given set of focal neurological deficits is essential for accurate acquisition and interpretation of neuroimaging. Relying on often-limited clinical information, neuroradiologists must choose the most appropriate imaging modality and tailor a study to best identify the culprit lesion to allow for accurate interpretation. Methods: A multiple-choice quiz was designed including clinical vignettes localizing to lesions within the central (CNS) and peripheral nervous systems (PNS). The quiz was pilot-tested and refined before distribution as an electronic survey to practicing neuroradiologists and fellows within newsletters from the American Society for Neuroradiology and Canadian Neurological Sciences Federation. Results: The quiz was begun by 45 neuroradiologists and completed in its entirety by 22. Most respondents were working at urban academic/teaching hospitals(81%) in the USA(42%). The majority (90%) report no clinical neurology rotation during their training. Respondents identified a high proportion (88%) of correct answers in questions about brainstem localizations. Fewer correct answers were selected in questions describing seizure semiology (44%) or flaccid weakness (59%). Conclusions: The small size of our study limits interpretation and generalizability of the findings. Identification of a potential gap in neuroradiology education relating to localization of more complex CNS and PNS presentations merits further exploration.